POTENTIAL DRUG-DRUG INTERACTIONS OF CARDIOVASCULAR DRUGS BASED ON LITERATURE IN GERIATRIC PATIENTS WITH CONGESTIVE HEART FAILURE AT Dr. M. DJAMIL PADANG HOSPITAL - PERMATASARI, DITA; HUSNA, NUR ALIMA; YOSMAR, RAHMI (International Journal of Applied Pharmaceutics, 2024)
Objective: Congestive Heart Failure (CHF) is a notable cardiovascular disease impacting global morbidity and mortality. Geriatric patients with CHF typically require multiple medications that can potentially cause drug-drug interactions and affect patient therapy outcomes. This study aims to determine the potential drug-drug interactions, the relationship between the average number of cardiovascular drugs per day and the potential drug-drug interactions, and the relationship between the severity of drug-drug interactions and the clinical symptoms and signs of the patients. Methods: The research method used was analytical observational with retrospective data collection through the medical records of inpatients in 2021. A total of 63 patients were included using the total sampling method. Results: Results revealed that furosemide was the most commonly prescribed cardiovascular medication (15.27%). Among the participants, 93.65% exhibited potential drug-drug interactions (332 occurrences), with the most frequent involving furosemide and bisoprolol (32 cases). Pharmacodynamic interactions were the dominant mechanism (85.24%), with moderate severity (65.06%) being common. A significant relationship existed between the average number of cardiovascular drugs per day and the potential drug-drug interactions (p<0.05). Nonetheless, there was no notable correlation discovered between the severity of the interaction and the presence of symptoms and clinical signs (p>0.05). Conclusion: When considering the high incidence of potential drug-drug interactions, it is expected that clinical pharmacists have the competence to analyze potential drug interactions to prevent harmful effects on patients.